EXCHANGE RATE POLICY, GROWTH, AND FOREIGN TRADE IN CHINA - Gligorić, Mirjana (Economic Annals, 2011)
This paper analyzes a hot topic: the influence of an undervalued currency on macroeconomic variables - primarily on the economic growth and trade balance of a country, but also on employment, foreign exchange reserves, competition, and living standards. It also reviews and explains the consequences of yuan undervaluation, points out the need for its appreciation, and states the negative effects that stem from this measure. Special attention is given to the problematic bilateral relations between China and the USA and the reasons why Americans are worried about the exchange rate policy that China implements. Although yuan appreciation would decrease the American foreign trade deficit, it also raises the question of further financing of the American deficit. There are also other problems that the possible appreciation would cause for the American economy, due to the effect of J-curve, pass-through, larger costs of input imported from China, etc. Therefore, Chinese foreign exchange policy is an important subject, but it is not the solution to the problems of the global economy – which have deeper roots than that. However, there is no excuse for China implementing unfair exchange rate policies, or replacing such policies with controversial protectionist policies (as some authors have suggested).